Strategi Corporate Social Responsibility PT. Kompas Gramedia dalam Menjaga Citra Perusahaan Melalui Program Kampung Koran - Illiyin, Rachell Aurell Azzaria; Utari, Syifa Astasia (Innovative: Journal Of Social Science Research, 2025)
Abstract Social and environmental responsibility as part of business ethics. Corporate Social Responsibility (CSR) is an important strategy in building and maintaining a company's image in the public eye. This study aims to analyze how the CSR strategy implemented by PT. Kompas Gramedia through the Kampung Koran program maintains the company's image. This study uses a descriptive qualitative approach. Data collection techniques were carried out through in-depth interviews and documentation. The theory used is the CSR strategy from Coombs and Holladay which includes five stages: scanning, conducting, creating, communicating, and evaluating. In addition, the image formation theory from John M. Tiedemann was also used to analyze the process of forming a company's image. The results show that the Kampung Koran Program of PT. Kompas Gramedia demonstrates a planned and participatory CSR strategy. Through scanning and monitoring as well as conducting formative initiatives, the company is able to map community needs and design programs based on local potential. At the create CSR stage, the focus is directed at empowering housewives with skills in processing used newspapers, then strengthened through communicate CSR with communicative narrative techniques that touch public emotions, and is periodically evaluated at the evaluation stage to maintain relevance and sustainability. This process contributes directly to the formation of the company's image. Starting with a creative idea to recycle newspapers, a positive perception emerged that the program brings tangible benefits. Keywords: Corporate Social Responsibility (CSR), Kampung Koran, Citra Company, Kompas Gramedia.